Interacting with Digital Memorials in a Cemetery: Insights from an Immersive Practice - Maciel, Cristiano; Carvalho Pereira, Vinicius; Leitão, Carla; Pereira, Roberto; Viterbo, José (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2018)
This research analyzes how users that are also HCI designers behave in the interaction with digital memorials linked to graves through QRCodes. We carried out an immersive practice in the Consolação Cemetery (São Paulo, Brazil), where QRCodes are used to tag graves of famous deceased people and to guide the visitors in the site. The QRCode tags link the graves to an online application for digital memorials called MemoriAll. This paper presents an overview of the study and its main results, promoting discussion on the topic.